PENGARUH MEDIA GAMBAR TERHADAP HASIL BELAJAR KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS V SD NEGERI 040451 KABANJAHE - Putri Br Taringan, Melisa; Yunistita Singarimbun; Juwita Tindaon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using image media on the learning outcomes of descriptive text writing skills of fifth-grade students at SD Negeri 040451 Kabanjahe. The background of this research is based on the low ability of students in writing descriptive texts, which is caused by the lack of the use of interesting and effective learning media in the teaching and learning process. This study uses a quantitative approach with an experimental method. The research design applied is the pretest-posttest control group design. The population of this study consists of all fifth-grade students at SD Negeri 040451 Kabanjahe, with samples selected using a specific sampling technique. The research instrument is a descriptive text writing test administered before (pretest) and after (posttest) the treatment. The results of the study indicate that there is a significant effect of using image media on students' learning outcomes in descriptive text writing skills. This is shown by the increase in the average scores of students after being given treatment using image media compared to before the treatment. In addition, the statistical test results show that the significance value is less than 0.05, so the research hypothesis is accepted. Based on the results of the study, it can be concluded that the use of image media is effective in improving students' descriptive text writing skills at SD Negeri 040451 Kabanjahe. Therefore, it is recommended that teachers use image media as an alternative in teaching writing to improve students' interest and learning outcomes.